2008
DOI: 10.1093/annhyg/men021
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Bioaerosols in Poultry Houses at Different Stages of Fattening; Use of Real-time PCR for Airborne Bacterial Quantification

Abstract: Previous studies have demonstrated that poultry house workers are exposed to very high levels of organic dust and consequently have an increased prevalence of adverse respiratory symptoms. However, the influence of the age of broilers on bioaerosol concentrations has not been investigated. To evaluate the evolution of bioaerosol concentration during the fattening period, bioaerosol parameters (inhalable dust, endotoxin and bacteria) were measured in 12 poultry confinement buildings in Switzerland, at three dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(34 citation statements)
references
References 27 publications
2
32
0
Order By: Relevance
“…Culturing methods require a growth medium, which may not satisfy the specific growth requirements of all species of interest, and also requires prolonged incubation (i.e., >24 hours) 16 . Recently, detection and enumeration of airborne microorganisms has been accomplished using techniques based on polymerase chain reaction (PCR) and enzyme-linked immunosorbent assays (ELISA), which are highly sensitive and quantitative techniques 17 18 19 20 21 . However, additional pretreatment processes (such as particle condensation/purification), and elaborate sample handling by well-trained operators in a clean environment are required 22 .…”
mentioning
confidence: 99%
“…Culturing methods require a growth medium, which may not satisfy the specific growth requirements of all species of interest, and also requires prolonged incubation (i.e., >24 hours) 16 . Recently, detection and enumeration of airborne microorganisms has been accomplished using techniques based on polymerase chain reaction (PCR) and enzyme-linked immunosorbent assays (ELISA), which are highly sensitive and quantitative techniques 17 18 19 20 21 . However, additional pretreatment processes (such as particle condensation/purification), and elaborate sample handling by well-trained operators in a clean environment are required 22 .…”
mentioning
confidence: 99%
“…Several studies have shown a high level of biological hazards (bacteria, fungi, endotoxin and (1 → 3)-β-D-glucan) associated with large-scale farming of animals in Poland (Bródka et al, 2012; Cyprowski et al, 2012; Sowiak et al, 2012a, 2012b; Szadkowska-Stańczyk et al, 2010). Bacteria of the genus of Staphylococcus, Streptococcus, numerous Gram-negative and Gram-positive rod-shaped bacteria, including many species of Bacillus genus, were found in bacterial aerosols coming from hen-houses (Vučemilo et al, 2007; Zucker et al, 2000; Oppliger et al, 2008). Respiratory and systemic symptoms and declines in lung function have been associated with endotoxin exposure in farm workers (Heederik et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…It is possible that the results would differ for dusts collected using a different sampling method. Reports summarizing dust characterization and exposure studies have used a myriad of sample collection strategies including static cloths (Ege et al, 2012), air sampling (Oppliger et al, 2008) and brush collection (Wyatt et al, 2008). However, an understanding of settled dust particles would provide insight into the nature and interactions of larger dust constituents which are more likely to accumulate and persist within animal production housing.…”
Section: Discussionmentioning
confidence: 99%